A study on resistance to change among employees in private sector / Noor Hafizah Jamil - Jamil, Noor Hafizah (2014)
This research is deeply focused on to identify the most common factors that contribute people resist to change and to identify the existence of resistance to change among employees. The research method that used in this research is questionnaire that had been distributed to get the result from the respondent in order to analyze all the factors in changing. It was discovered that resistant to change in company occurs due to the several factors which are fear of failure and uncertainty avoidance towards the technology and management. From this study, it is identified that education and communication, foster open communication, participation and involvement, facilitation and support, negotiation and agreement, manipulation and co-option and implicit and explicit coercion are the ways to manage the problem of resistance to change. The response that researcher received for this study of I 00 employees from Unisem (M) Berhad, Simpang Pulai, Perak. The sampling technique that has been used by researcher is simple random sampling and the researcher used the sample of respondents to get the result of data collected.This paper can be concluded that resistance to change is the major problem in the organization and each firm experienced it. The way of the organization to handle and manage their employees as well as their firm is the solution to ensure everyone are follow the rules and changes.